Microbial Interactions in the Phyllosphere Increase Plant Performance under Herbivore Biotic Stress - Saleem, Muhammad; Meckes, Nicole; Pervaiz, Zahida H.; Traw, Milton B. (Frontiers in Microbiology, 2017)
The phyllosphere supports a tremendous diversity of microbes and other organisms. However, little is known about the colonization and survival of pathogenic and beneficial bacteria alone or together in the phyllosphere across the whole plant life-cycle under herbivory, which hinders our ability to understand the role of phyllosphere bacteria on plant performance. We addressed these questions in experiments using four genetically and biogeographically diverse accessions of Arabidopsis thaliana, three ecologically important bacterial strains (Pseudomonas syringae DC3000, Xanthomonas campestris, both pathogens, and Bacillus cereus, plant beneficial) under common garden conditions that included fungus gnats (Bradysia spp.). Plants supported greater abundance of Bacillus cereus over either pathogenic strain in the phyllosphere under such greenhouse conditions. However, the Arabidopsis accessions performed much better (i.e. early flowering, biomass, siliques and seeds per plant) in the presence of pathogenic bacteria rather than in the presence of the plant beneficial Bacillus cereus. As a group, the plants inoculated with any of the three bacteria (Pst DC3000, Xanthomonas, or Bacillus) all had a higher fitness than uninoculated controls under these conditions. These results suggest that the plants grown under the pressure of different natural enemies such as pathogens and an herbivore together perform relatively better, probably because natural enemies induce host defense against each other. However, in general, a positive impact of Bacillus on plant performance under herbivory may be due to its plant-beneficial properties. In contrast, bacterial species in the mixture (all three together) performed poorer than as monocultures in their total abundance and host plant growth promotion, possibly due to negative interspecific interactions among the bacteria. However, bacterial species richness linearly promoted seed production in the host plants under these conditions, suggesting that natural enemies diversity may be beneficial from the host perspective. Collectively, these results highlight the importance of bacterial community composition on plant performance and bacterial abundance in the phyllosphere.